Evaluation and toxicity of iron and manganese in lettuce (Lactuca sativa L.): bioaccumulation and oxidative damage - Kelechi, Blessing Jumoke (2023)
The disaster with the Fundao dam in Mariana, MG, Brazil, launched tons of iron ore tailings into the environment, which elevated the levels of iron and manganese in the mining area. Thus, it is imperative to understand how these metallic elements pollutant can buildup in lettuce and also the oxidative damage this pollutant can cause to the lettuce plant. Therefore, we investigated the bioaccumulation, the toxicity symptoms and the oxidative damage of this elements on lettuce. The specimens were subjected to four treatments: control (nutrient solution only); Fe (5 mM Fe-EDTA); Mn (4 mM MnCl 2 ); Fe + Mn, which were assessed at 2 nd day of exposure to treatments. Physiological and biochemical related analysis were performed. The results showed that lettuce plants cannot undergo Fe and Mn metal stress without showing toxicity symptoms. Although the toxicity exhibited by Fe treated plants was more severe than Mn treated plant. Also, the accumulation of the elements in the plant was not altered by their association, it has cumulative effects on the plant and are not competitive in the absorption process. The translocation of Fe from the roots to the leaves was high meanwhile Mn translocation to the leaves was low. Furthermore, a remarkable antioxidant enzymes activity was observed in all treatments but the ROS produced due to the oxidative stress could not be scavenge which led to oxidative damage especially in the Fe isolated and combined treated plants compared to Mn treated plant. Keywords: Reactive oxygen species. Oxidative stress. Antioxidant enzymes. Mining residue.